Faculty diversity, equity, and inclusion in academic dentistry: Revisiting the past and analyzing the present to create the future. Issue 9 (27th September 2022) - Cain, Lisa; Brady, Michelle; Inglehart, Marita R.; Istrate, Emilia C.
Abstract: Aim: In 2021, NIDCR published the landmark report "Oral Health in America." It described that while oral health‐related research and care has seen amazing progress, oral health inequities and lack of oral care for large segments of the US population have not improved. This situation plus the predicted increase of the diversification of the US population requires decisive actions to ensure that future dentists will be optimally prepared to provide the best possible care for all patients. A diverse dental educator workforce plays a crucial role in obtaining this goal. The objectives of this document were threefold. Aim 1 was to analyze past and current trends in the diversity and inclusion of historically underrepresented ethnic/racial (HURE) and marginalized (HURM) dental faculty members. Aim 2 focused on reviewing best practices and challenges related to achieving dental faculty and leadership diversity and inclusion. Aim 3 was to develop recommendations for increasing the diversity and inclusion of dental faculty in the present and future. Methods: An analysis of ethnicity/race and gender faculty data collected by the American Dental Education Association (ADEA) in 2011–2012 and 2018–2019 showed that achieving faculty diversity and inclusion has been an ongoing challenge, with limited success for faculty from HURE backgrounds. In order to create this much‐needed change, best practices to increase the applicant pool, change recruitment strategies, and develop solid retention and promotion efforts were described. Research discussing the challenges to creating such changes was analyzed, and strategies for interventions were discussed. Conclusion: In conclusion, evaluations of efforts designed to create a more diverse and inclusive work force is crucial. Institutions must evaluate their diversity data, practices utilized, and the policies implemented to determine whether the desired outcomes are achieved. Only then will the future dental workforce be optimally prepared to provide the best possible care for all patients in the United States.